Analisis Penerapan Sistem Informasi Akuntansi Persediaan Obat Dalam Pencegahan Kecurangan Pada Puskesmas Jampangkulon, Puskesmas Cibitung, Puskesmas Surade dan Puskesmas Buniwangi - Nurhasanah, Siti; Ismatullah, Ismet; Sofiani, Veniati (Universitas Muhammadiyah Yogyakarta, 2019)
This study to find out : 1) Accounting information system at the puskesmas. 2) prevention of fraud at the puskesmas. 3) the role of accounting information systems in fraud prevention. 4) contraints in implementing accounting information systems. The variable consits of an accounting information systems and fraud prevention. The method used in this study is a qualitative method with a descriptive approach. This research was conducted by observation and interviews with parties involved i the application of accounting information systems.The application of accounting information systems has been applied to three of the four health centers that have been studied. Although the four puskesmas have the sam contraints in implementing accounting information systems, namely the lack of human resourcesan advice on infrastructure that supports the implementation of this systems. Fraud prevention applied to each puskemas is the same, namely by giving a warning letter to employees who commit fraud.